Thiopental is better than propofol for electroconvulsive therapy - Nuzzi, Massimiliano; Delmonte, Dario; Barbini, Barbara; Pasin, Laura; Sottocorna, Ornella; Casiraghi, Giuseppina Maria; Colombo, Cristina; Landoni, Giovanni; Zangrillo, Alberto (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: electroconvulsive therapy is a psychiatric procedure requiring general anesthesia. The choice of the hypnotic agent is important because the success of the intervention is associated to the occurrence and duration of motor convulsion. However, all available anesthetic agents have anti-convulsant activity. We compared the effect of thiopental and propofol on seizures. Methods: We designed a retrospective study at Mood Disorders Unit of a teaching Hospital. Fifty-six consecutive patients undergoing electroconvulsive therapy were enrolled. Patients received fentanyl followed by either thiopental or propofol. We evaluated the incidence and the duration of seizure after electric stimulus at the first session of electroconvulsive therapy for each patient. Adverse perioperative effects were recorded. Results: Patients were 60±12.1 years old and 64% was female. There was a statistically significant higher number of patients who had motor convulsion activity in the thiopental group when compared to the propofol group (25 vs 13, p=0.023). Seizure duration was statistically significant longer in the thiopental group than in the propofol group (35 sec vs 11 sec, p=0.046). No hemodynamic instability, oxygen desaturation episodes, prolonged recovery time from anesthesia and adverse effects related to anesthesia were recorded. Conclusions: Thiopental induction has a favourable effect on seizure when compared to propofol in patients undergoing electroconvulsive therapy.